Optimalisasi Biaya Transportasi Pendistribusian Pupuk Bersubsidi Menggunakan Model Transportasi Metode Modified Distribusition (MODI) - Hajar; Pertiwi, N; Jaya, A I (Program Studi Matematika, Universitas Tadulako, 2020)
ABSTRACT This study was conducted to obtain the optimal transport costs in the distribution of subsidized fertilizer in PT. GCS and PT.PPI. This research was done in two steps is to create a transport model of the data obtained and determine its solution initially with Least Cost method, and determine the optimal solution with ModifiedDistribution (MODI) method. Based on research that obtained the initial solution is Rp. 65.040.000 and optimal solution is Rp. 64.950.000. While the cost of transportation from the company is RP. 70.500.000. This shows that both distributors can optimize the total cost of transport for the distribution of subsidized fertilizer in January 2017 with the distribution cost savings of Rp. 5.550.000. Keywords : Least Cost Method, Modified Method of Distribution, Optimization, Transportation